Effect of multispecies probiotics on irritable bowel syndrome: A randomized, double‐blind, placebo‐controlled trial. Issue 1 (January 2014) - Yoon, Jun Sik; Sohn, Won; Lee, Oh Young; Lee, Sang Pyo; Lee, Kang Nyeong; Jun, Dae Won; Lee, Hang Lak; Yoon, Byung Chul; Choi, Ho Soon; Chung, Won‐Seok; Seo, Jae‐Gu
Abstract Background and Aim The efficacy of treatment with multispecies probiotics on irritable bowel syndrome (IBS) symptoms and the alterations of gut microbiota in patients who have taken probiotics were investigated. Methods This randomized, double‐blind, placebo‐controlled trial involved 49 IBS patients (probiotics: 25, placebo: 24) diagnosed according to the Rome III criteria. Patients were randomly assigned to two groups: either to receive multispecies probiotics (a mixture of Bifidobacterium longum, B. bifidum, B. lactis, Lactobacillus acidophilus, L. rhamnosus, and Streptococcus thermophilus) twice a day for 4 weeks or to receive a placebo twice a day for 4 weeks. The primary efficacy end‐point was the proportion of participants whose IBS symptoms were substantially relieved at week 4. Secondary end‐points were the intensity of abdominal pain/discomfort, bloating, stool frequency/consistency, alterations in fecal microflora over the 4 weeks. Fecal microflora were analyzed in 34 patients (probiotics: 17, placebo: 17) by quantitative real‐time polymerase chain reaction assays. Results The proportion of patients whose IBS symptoms were substantially relieved at week 4 was significantly higher in the probiotics group than in the placebo group: 68.0% (17/25) versus 37.5% (9/24) (P < 0.05). Secondary end‐points such as improvement in abdominal pain/discomfort and bloating occurred in the probiotics group but not in the placebo group. Fecal analysis revealed that B. lactis, L. rhamnosus, and S. thermophilus had increased significantly in the probiotics group after 4 weeks and that B. lactis had increased in the placebo group. Conclusions Multispecies probiotics are effective in IBS patients and induce the alterations in the composition of intestinal microbiota.